Religions of the world - Hopfe, Lewis M. (Pearson Education, 2016)
The histories, deep-seated beliefs, and ethical systems that make up the world's religions are some of the most important forces at play on our incredibly diverse planet. Religions of the World, Thirteenth Edition guides students as they explore each of the world's major faiths, imparting the knowledge they need to better understand today's world. By explaining religious diversity and complex themes within a historical context, Religions of the World helps students relate to cultures very different from their own.